Nonthermal atmospheric plasma enhances myoblast differentiation by eliciting STAT3 phosphorylation. Issue 3 (14th December 2018) - Park, Ju Kyeong; Kim, Yeon Soo; Kang, Sung Un; Lee, Yun Sang; Won, Ho-Ryun; Kim, Chul-Ho
ABSTRACT: The use of nonthermal atmospheric plasma (NTP) in the biomedical field has recently expanded into cell death induction in cancer, infection prevention, inflammation treatment, and wound‐healing enhancement. NTP has been demonstrated to enhance skin and muscle regeneration, but its effects on tissue regeneration, following deep tissue or muscle damage, remains underinvestigated. In this study, we determined the effects of NTP on muscle differentiation and the mechanisms of NTP's contribution to differentiation and regeneration. NTP treatment enhanced cell differentiation in primary normal human skeletal muscle myoblast cells and increased the relative expression of mRNA levels of MyoD which is one of the earliest markers of myogenic commitment, and myogenin, which are important transcription factors required for myogenic differentiation. Furthermore, NTP treatment induced increases in the levels of myosin heavy chain, a differentiated muscle‐specific protein, and in myotube formation of myoblasts. We observed that signal transducer and activator of transcription 3 (STAT3) activation induced by NTP treatment affects the myogenic differentiation. In addition, STAT3 phosphorylation was also enhanced by NTP treatment in injured animal muscle. These findings indicate that NTP could enhance musculoskeletal differentiation by acting as an external stimulus for myoblast differentiation, suggesting its treatment potential in promoting regeneration of damaged muscle.—Park, J. K., Kim, Y. S., Kang, S. U., Lee, Y. S., Won, H.‐R., Kim, C.‐H. Nonthermal atmospheric plasma enhances myoblast differentiation by eliciting STAT3 phosphorylation. FASEB J. 33, 4097–4106 (2019). www.fasebj.org